Helen Barrett Montgomery: the global mission of domestic feminism - Mobley, Kendal P. (Baylor University Press, 2009)
Helen Barret Montgomery : the interpretive challenge -- "The fatherhood of God and the victorian family" : the childhood and early education of Helen Barrett -- Evangelism, progressivism, and domesticity : Helen Barrett's Wellesley -- The new woman at work, home, and in public : Helen Barrett Montgomery's return to Rochester -- Montgomery's "new woman" and the limitless scope of woman as citizen -- Susan B. Anthony and Helen Barrett Montgomery : an intergenerational feminist partnership -- The Rochester Women's Educational and Industrial Union : Montgomery's platform for municipal housekeeping -- Helen Barrett Montgomery, Walter Rauschenbush, and the battle for progressive public education -- The Hackett House episode and the birth of social centers -- "A great theme" : domestic feminism and the gospel of the women's jubilee -- After the jubilee : women's colleges and "world friendship" -- A "middle-of-the-road Baptist" : creedalism and the defense of Baptist liberty